Bow Saw V/S Axe for Pulpwood Billetting - Sethi, Y. R. (Indian Forester, 1976)
With a view to maximizing the utilization of standing volume of pulpwood species by decreasing the wastage involved in billetting and making more raw-material available, from the same source, to the growing Pulp &Paper industry in the country, an experiment has been conducted, at the F.R.I., to find out a suitable hand tool which would be used for this purpose, A study has been conducted to compare the efficiency of our axe, which is extensively used for billetting with an imported bow Saw for making pulpwood billets. The study has revealed that by using a bow saw instead of an axe we can increase the efficiency of the worker by about 100% and decrease the wastage involved in pulpWood harvesting to its minimum.